2007
DOI: 10.1159/000098545
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of the Simultaneous Secretion of Melatonin and Leptin during Normal Puberty

Abstract: Background/Aims: Pubertal changes are a consequence of the activation of the hypothalamic-pituitary-gonadal axis due to an increase in the frequency and magnitude of pulses of gonadotropin-releasing hormone (GnRH), which may depend on the intrinsic properties of the neurons of the hypothalamic arcuatus nucleus, or on the influence of neurotransmitters and/or neuromodulators. We evaluated the serum concentrations of melatonin and leptin in healthy prepubertal and adolescent subjects of both sexes, to define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 87 publications
0
15
0
1
Order By: Relevance
“…Only the isoform OBRb is considered to be capable of signal transduction across the cell membrane 6 . The concept of metabolic programming is a permanent change related to a particular function, as a result of some event which occurs during the perinatal period 7 . Several animal experiments have shown that hormones as leptin and nutrition status, which affect development during sensitive periods early in life, permanently program the structure and function of body tissues and systems [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Only the isoform OBRb is considered to be capable of signal transduction across the cell membrane 6 . The concept of metabolic programming is a permanent change related to a particular function, as a result of some event which occurs during the perinatal period 7 . Several animal experiments have shown that hormones as leptin and nutrition status, which affect development during sensitive periods early in life, permanently program the structure and function of body tissues and systems [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…It informs the brain about whether there are sufficient energy stores to initiate reproductive functions (38). Increases in serum leptin levels have been observed around the beginning of the menarche (39) or the estrous cycle (40). Therefore, it is generally accepted that leptin is essential in the induction of puberty in the female.…”
Section: Discussionmentioning
confidence: 99%
“…6-OHMS is the major enzymatic metabolite of melatonin [48] and has frequently been shown to correlate with serum melatonin concentrations [34,35]. The well-documented rapid fall of melatonin levels in serum from childhood to puberty [47] is mainly correlated with an increase in body mass during that period with a corresponding increase in serum volume rather than a decreasing melatonin production, analyzed here with 24-hour urine samples. Thus, mean urinary 6-OHMS excretion, and therefore melatonin production, remained relatively stable in our subjects between the ages of 4 and 19 years, as previously shown by Griefahn et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…As melatonin production is suppressed by light [13], we controlled for the season in which the urine collection took place. As body composition could also have an influence on melatonin secretion [47], the variables age, BMI-SDS, overweight and percent body fat were considered as potential confounders. For these variables, we considered the values at baseline and their interaction with time, and the change in the values during the study period.…”
Section: Methodsmentioning
confidence: 99%